Emotions, crisis, and institutions: Explaining compliance with COVID-19 regulations - Danqi Guo; Sabrina Habich-Sobiegalla; Genia Kostka (Regulation & Governance, 2023)
Amid the COVID-19 pandemic, citizens' compliance with government preventive measures was one of the top policy priorities for governments worldwide. This study engages with socio-legal and psychological theories on compliance and proposes an analytical framework to explore the role of different psychological factors on individual-level compliance during global health crises. Using the results of three national surveys, we argue that various negative emotional states, perceptions of the ongoing crisis, and of the institutional settings are major factors influencing individual compliance across countries. Most importantly, while increased panic, anxiety, and sadness lead to higher compliance, rising anger, loneliness, and impatience decrease compliance levels. Notably, perceptions of the COVID-19 crisis—especially health concerns and a worsening financial situation—tend to elicit anger among citizens across countries, thereby further hampering their obedience with pandemic regulations. Furthermore, perceptions of public institutions also influence individual compliance. Overall, in order to ensure compliance, we suggest that policymakers and those implementing government measures take individual psychological factors into account both within and beyond the public crisis context.
Keywords: 330; compliance; COVID-19 measures; crisis perceptions; emotions; institutional perceptions